Media framing of spiders may exacerbate arachnophobic sentiments. Issue 4 (31st August 2020) - Mammola, Stefano; Nanni, Veronica; Pantini, Paolo; Isaia, Marco
Abstract: Spiders are able to arouse strong emotional reactions in humans. While spider bites are statistically rare events, our perception is skewed towards the potential harm spiders can cause to humans. Nevertheless, there is still limited understanding of the role of the media in spreading (mis)information about them thereby promoting this distorted perception of risk. We examined the human dimension of spiders through the lens of traditional media, by analysing spider‐related news published online in Italian newspapers between 2010 and 2020 ( n = 314). We assessed the accuracy, circulation and sensationalistic content of each article, and assessed how each of these features drove news' share on social media. We observed a recent, exponential increase in the frequency of the news, particularly those focused on medically important spiders—the Mediterranean black widow Latrodectus tredecimguttatus and the Mediterranean recluse Loxosceles rufescens . The news quality was generally poor: 70% contained different types of error, 32% were sensationalistic, and in virtually none was an expert consulted. The risk scenario depicted by the media reports was unnecessarily alarmist, especially with regard to L. rufescens . A conservative estimate would suggest that less than 10% of the bites reported in the media reports analysed here were delivered by the species described in the report. Moreover, two out of three casualties associated with a bite of the Mediterranean recluse were fake news, while the third was unverifiable. Overstated news referring to spider bites was shared significantly more on social media, thus contributing to frame a distorted perception of the risk. This is important given that these negative sentiments may ultimately lead to lowering public tolerance towards spiders and reducing conservation efforts towards them. We discuss open questions and avenues for future research concerning the media coverage of widely feared animals, that will help bridge knowledge gaps regarding the role of traditional and social media in framing our perception of the natural world. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Riassunto: I ragni sono organismi in grado di suscitare forti reazioni emotive. Sebbene i loro morsi siano eventi statisticamente rari, esiste una diffusa paura riguardo ai ragni anche in aree del pianeta dove non sono presenti specie pericolose per l'uomo. Tale percezione distorta del rischio potrebbe essere in parte dovuta alla diffusione mediatica di informazioni imprecise sui ragni. Abbiamo indagato questo fenomeno in Italia, andando a valutare la correttezza, la diffusione e il contenuto sensazionalistico di più di 300 notizie pubblicate su giornali e riviste online tra il 2010 e il 2020. Per ogni articolo, abbiamo stimato statisticamente come ciascuno di questi fattori agisca sulla diffusione delle notizie sui social media (Facebook). Vi è stato un recente aumento nella frequenza di notizie sui ragni in Italia, specialmente quelle incentrate sulle due specie di rilevanza medica in Italia ‐ la vedova nera mediterranea Latrodectus tredecimguttatus ed il ragno violino Loxosceles rufescens . L'attendibilità delle notizie è risultata generalmente bassa: il 70% conteneva diversi tipi di errori, il 32% era di carattere sensazionalistico e quasi in nessun caso era stato consultato un esperto. Una significativa porzione degli articoli forniva una rappresentazione allarmistica e distorta del rischio associato ai morsi di ragni, soprattutto nel caso del ragno violino. Una stima prudente suggerirebbe come meno del 10% dei morsi riportati negli articoli siano effettivamente attribuibili alle specie menzionate. Inoltre, le sporadiche notizie inerenti morsi fatali di ragno violino erano o false o non verificabili. Le notizie a carattere sensazionalistico erano, inoltre, maggiormente condivise sui social media, contribuendo così a generare una percezione distorta del rischio associato ai morsi di ragno. Sul lungo periodo, questo fenomeno potrebbe portare ad un'ulteriore stigmatizzazione dei ragni ed ad una riduzione degli sforzi di conservazione nei loro confronti. Il nostro lavoro apre la strada a future ricerche riguardanti la copertura mediatica di animali ritenuti pericolosi, andando a disvelare il ruolo che i media svolgono nella nostra percezione del mondo naturale.